Operational services management in the context of sustainable development of intelligent technologies. Issue 1 (July 2020) - Romanova, Anna; Evgeniya, Ilina
Abstract: The article discusses the conditions for the functioning of a sustainable economy. The operation of an apartment building is considered for this stage of economic development not as an object of luxury, but as a basic need to live comfortably. The object of the study is the level of depreciation and technical "under-equipping" of apartment buildings. In the conditions of sustainable development of intelligent technologies, theoretical understanding of economic efficiency from the introduction of innovative technologies in the field of housing and communal services, as well as improving indicators affecting the quality of services provided by industry enterprises, which is directly related to the livelihoods of the population, is no less relevant. The article discusses the experience of practical application of innovative solutions in the field of operational services of an apartment building. The purpose of the study is to analyze innovative technologies in the field of housing and communal services and an objective review of specific examples of the introduction of innovations in the industry.